THE TEACHER'S PERSPECTIVE ON ADHD - Almeida, Flávia Silva de; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
At first, the aim of this paper is to explore and clarify scientific information about behavior, causes, characteristics, among other aspects, in the "biopsychosocial" area, on individuals with Attention Deficit and Hyperactivity Disorder – ADHD. However, the ADHD, as a problem identified by inattention, hyperactivity/ impulsivity (phisical and mental), requires, in turn, and important analysis, case by case. So, according to consulted bibliography, it is allowed to say that there are still great difficulties in giving a diagnosis, especially on children, considering levels/ degrees of various aspects and, yet understanding that, on adults, the symptoms tend to be less intense. But, also believing that, in the education field, there are still professionals in need of major knowledge, who give diagnosis (neglect), causing letterings on certain individuals (students), we made use of researches to demonstrate not only the universe of the ADHD, but also verifying an/ or identifying the inclusion of children with that disorder at schools.